Impact of hybrid working systems on employee wellbeing in professional services firms: a case study of PricewaterhouseCoopers in Nairobi, Kenya - Nyambego, O. R. (Strathmore University, 2024)
The maintenance of a safe and healthy work environment for all the employees and the organization itself, as well as the people working for the organization, contributes to sustainability of organizations. Organizations that have embedded employee wellbeing at the workplace have chronicled the business success as well. For individuals, workplace wellbeing stands for a full, non-stop duty for both the employer and employees. Hybrid working system is an adaptable mode of implementation that, besides working in an office environment, also gives the option of working remotely. Flexibility is different depending on the hybrid working environment, thus giving rise to a different range of schedules. Companies may design their hybrid work model to create a more comfortable working environment that gives a better work-life balance to the employees. It becomes a source for new ideas and active dialogue which in turn lead to productivity and employee engagement at work. The study was to assess the impact of hybrid working systems on employee wellbeing in professional services firms: A case study of PricewaterhouseCoopers in Nairobi, Kenya with specific objectives being; To establish the influence of hybrid working systems of professional services firms: a case of PwC in Nairobi, Kenya; to investigate the effect of building flexible infrastructure on employee well-being in professional services firms in Nairobi Kenya, PwC; to establish the impact of physical working environment on employees wellbeing of professional services firms in Nairobi Kenya, PwC; and to establish the impact of remote working on employees well-being of professional services firms in Nairobi Kenya, PwC. Through the assessment of this topic and the variables there was fulfillment of the mission aligned with hybrid work practices such as infrastructure building, tie-in of human resource and information technology, the creation of a correct work environment, and connecting offsite and onsite employees. The study adopted Job Demand resources theory and Self-Determination theory constituting, of the basis upon which the study was grounded. The study targeted all the employees of PwC in Nairobi, Kenya as the target population. The study applied a research philosophy of positivism and a descriptive cross-sectional survey was used as the research design. Data collection instrument used was questionnaires which consisted of both open and close questions, and the procedure adopted was a handed out in a drop and pick technique. Collected data was subjected to descriptive and inferential statistics analysis, while qualitative research was gathered using interviews which was further analyzed using NVIvo using thematic approach. In establishing the relationship between the variables the study used multiple regression model. The study utilized both qualitative and quantitative data approaches to help identify the key findings. The results, after careful analysis and examination, revealed that flexible work environment, physical work environment, and remote working impact on employee well-being within professional service firms. The results yielded crucial insights into optimizing workplace conditions for enhanced employee satisfaction and productivity. The findings underscore the multifaceted nature of employee well-being, elucidating how various aspects of the work environment contribute to overall satisfaction and fulfillment. With a notable portion of the variability in employee well-being explained by these factors, it becomes evident that organizations must prioritize creating conducive work environments that cater to the diverse needs and preferences of their workforce. The study suggested a future research to be conducted in the same area but employing a longitudinal or experimental designs, utilize multi-source data collection methods, incorporate qualitative approaches, conduct comparative studies across industries and geographic regions, implement intervention studies to evaluate the effectiveness of specific interventions, and explore mediation and moderation analysis to uncover underlying mechanisms and boundary conditions influencing the relationships under investigation. Addressing these limitations and pursuing further research in these areas would contribute to a more comprehensive understanding of the complex interplay between work environment factors and employee well-being in professional services firms.
Full - text thesis